A Clinical and Confocal Microscopic Comparison of Transepithelial PRK and LASEK for Myopia - Safak Korkmaz; Kamil Bilgihan; Sabahattin Sul; Ahmet Hondur (Journal of Ophthalmology)
Purpose. To compare the clinical and confocal microscopic results of transepithelial PRK versus LASEK for correction of myopia. Materials and Methods. Twelve patients with myopia received transepithelial PRK in one eye and LASEK in the other. In transepithelial PRK-treated eyes, the corneal epithelium was removed with 40 microns of excimer laser ablation and in LASEK-treated eyes with 25-second application of 18% ethanol. Time to epithelial healing, ocular discomfort, uncorrected and best corrected visual acuities, manifest refraction, haze, greyscale value, and keratocyte apoptosis in confocal microscopy were recorded. Results. The mean time to epithelial healing was significantly longer after LASEK (4.00 ± 0.43 versus 3.17 ± 0.6 days). On day 1, ocular discomfort was significantly higher after transepithelial PRK. The grade of haze, keratocyte apoptosis, and greyscale value in confocal microscopy were significantly higher in transepithelial PRK-treated eyes at 1 month. All transepithelial PRK- and LASEK-treated eyes achieved 20/25 or better UCVA and were within ±1.00 D of emmetropia at final visits. Conclusions. Both transepithelial PRK and LASEK offer effective correction of myopia at 1 year. However, LASEK appeared to induce less discomfort and less intense wound healing in the early postoperative period.